2012
DOI: 10.1371/journal.pone.0033750
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Characterization of the MicroRNA-Specific C. elegans Argonautes alg-1 and alg-2

Abstract: The genes alg-1 and alg-2 (referred to as “alg-1/2”) encode the Argonaute proteins affiliated to the microRNA (miRNA) pathway in C. elegans. Bound to miRNAs they form the effector complex that effects post-transcriptional gene silencing. In order to define biological features important to understand the mode of action of these Argonautes, we characterize aspects of these genes during development. We establish that alg-1/2 display an overlapping spatio-temporal expression profile and shared association to a miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
93
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(99 citation statements)
references
References 46 publications
6
93
0
Order By: Relevance
“…First, tissue specific knockdown of alg-1 was performed in the cells of the somatic gonad. Expression of alg-1 and alg-2 has been analyzed extensively (Tops et al, 2006; Vasquez-Rifo et al, 2012). alg-1 is expressed from early embryogenesis to adulthood in most, if not all, cells (Tops et al, 2006) and both alg-1 and alg-2 are expressed in the cells of the somatic gonad (Vasquez-Rifo et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…First, tissue specific knockdown of alg-1 was performed in the cells of the somatic gonad. Expression of alg-1 and alg-2 has been analyzed extensively (Tops et al, 2006; Vasquez-Rifo et al, 2012). alg-1 is expressed from early embryogenesis to adulthood in most, if not all, cells (Tops et al, 2006) and both alg-1 and alg-2 are expressed in the cells of the somatic gonad (Vasquez-Rifo et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, mature miRNAs exert their repressive function in association with a member of the Argonaute (Ago) protein family (reviewed by Iwakawa and Tomari, 2015), and the removal of this Ago effector protein has also been a useful tool for assessing the contribution of miRNA-mediated repression to different processes. For instance, in Caenorhabditis elegans, zygotic removal of both miRNA-dedicated Argonautes, ALG-1 and ALG-2, causes embryonic arrest during morphogenesis (Vasquez-Rifo et al, 2012). In mice, two Ago2 null alleles lead to developmental arrest around embryonic day (E) 5.5 or 7.5 (Alisch et al, 2007;Morita et al, 2007), and loss of Dicer1 also causes early embryonic lethality, with animals arresting before E7.5, prior to the body plan being established (Bernstein et al, 2003); however, it should be noted that Dicer is also involved in the endo siRNA pathway, so a contribution from this other class of small RNAs should be considered in the interpretation of such experiments.…”
Section: Introductionmentioning
confidence: 99%
“…To ascertain whether microRNAs regulate nicotine-dependent behavior, we tested alg-1 mutant worms for acute and withdrawal responses. ALG-1, a member of the Argonaute family, is a key component of the microRNA-induced silencing complex (miRISC) and is required for microRNA activity (Vasquez-Rifo et al, 2012). We found that alg-1 mutant worms were severely defective in nicotine withdrawal (Fig.…”
Section: Resultsmentioning
confidence: 99%